Observations on the biology of Afro–tropical Hesperiidae (Lepidoptera) principally from Kenya. Part 1. Introduction and Coeliadinae - Cock, Matthew J. W. (Zootaxa, 2010)
Partial life histories for eight Afro–tropical Coeliadinae are described and illustrated: Pyrrhochalcia iphis (Drury) (Côte d’Ivoire), Pyrrhiades lucagus (Cramer) (Ghana), P. anchises anchises (Gerstaecker) (Kenya), Coeliades chalybe chalybe (Westwood) (Côte d’Ivoire), C. forestan forestan (Stoll) (Kenya), C. pisistratus (Fabricius) (Kenya), C. sejuncta (Mabille & Vuillot) (Kenya), C. kenya Evans stat. rev. (Kenya). Descriptions of a further six species or subspecies are provided from the literature: P. anchises jucunda (Butler) (Oman), P. aeschylus (Plötz) (Republic of Guinea), P. pansa (Hewitson) (Réunion), C. bixana Evans (Democratic Republic of the Congo), C. libeon (Druce) (Democratic Republic of the Congo), C. keithloa (Wallengren) (South Africa), C. lorenzo Evans stat. rev. (South Africa). Unpublished photographs provided by T.C.E. Congdon illustrate early stages of C. sp. probably fervida (Butler) and C. rama Evans (Madagascar). Notes based on museum material are presented for C. ramanatek (Boisduval). Generalisations are made for the subfamily in Africa and the implications for generic groupings in the subfamily are considered. All except C. libeon are known4 · Zootaxa 2547 © 2010 Magnolia Pressto feed on at least one species of Malpighiaceae, while C. libeon feeds on at species of at least two other families of Malpigiales. A new type of leaf shelter, the four–cut shelter, is introduced, characteristic of African Coeliadinae.